INTERPERSONAL COMMUNICATION OF HUSBAND-WIFE COUPLES IN OVERCOMING BABY BLUES SYNDROME POSTBIRTH MOTHER - Meybriana Maranu (Tadulako Social Science and Humaniora Journal, 2023)
Married couples facing the birth of their first child certainly have to adapt to various changes in roles and responsibilities. Especially with my wife's condition with baby blues syndrome. Through this research, researchers want to know how interpersonal communication between husband and wife is after the birth of their first child with baby blues syndrome. This research is a type of qualitative descriptive research. Informants in this research used interview and observation techniques. The research informants were 2 husband and wife couples who had just had their first child and their wives both experienced baby blues syndrome. The results of this research show that there have been changes in interpersonal communication between husbands and wives who experienced baby blues syndrome after giving birth to their first child. The nature of dishonesty and openness is a factor in the message not being conveyed well. After the birth of their first child, the husband and wife's interpersonal communication was ineffective because it was influenced by baby blues syndrome which caused physical fatigue, as well as emotional changes for the wife. After all, they were the ones who cared more about the baby. Various problems that arise choose to resolve the conflict with alternatives, disorientation, segmentation & integration